Potential of Artesunate in the treatment of visceral leishmaniasis in dogs naturally infected by Leishmania infantum: Efficacy evidence from a randomized field trial. - Hacène Medkour; Idir Bitam; Younes Laidoudi; Ismail Lafri; Abdelaziz Lounas; Hamza Karim Hamidat; Abdeslam Mekroud; Marie Varloud; Bernard Davoust; Oleg Mediannikov (Public Library of Science (PLoS), 2020)
Leishmaniasis is among the world's most neglected diseases. Dogs are the main reservoirs/hosts of Leishmania infantum, causative agent of both canine and human visceral leishmaniosis. Canine leishmaniasis (CanL) represents a public health problem as one of the most prevalent zoonotic diseases worldwide. Current therapeutics present drawbacks; thus, there is a need for more effective, safer, and cheaper drugs. The aim of this study was to evaluate and to compare the efficacy of oral administration of artesunate or meglumine antimoniate/allopurinol in dogs with clinical leishmaniasis. Forty-two dogs with naturally occurring clinical leishmaniasis were included in this open-label, simple randomized positive-control clinical field trial with 6 months of follow-up. Dogs received meglumine antimoniate 100 mg/kg/day and allopurinol 30 mg/kg/day for 28 days (control group, n = 26) or artesunate 25 mg/kg/day for 6 days (test group, n = 16). The animals were evaluated for their clinical evolution, parasite load (by qPCR) and humoral response at different time points: 0, 30, 90, and 180 days after treatment. Data analyses showed a significant improvement in both groups in clinical scores, parasitemia and antibody titers after treatment. Compared to the control group, the artesunate group showed significantly lower clinical score (P = 0.0001), lower parasitemia (P = 0.0001) and antibody titers after 6 months of follow-up. Compared to baseline values, a rapid, significant reduction (P < 0.012) in antibody levels, 2.28- versus 3.04-fold for the control versus artesunate groups, respectively, was observed 30 days after treatment. Antibody levels continued to decrease further in the artesunate group, where 58% of cases became seronegative at the 6-month follow-up. All qPCR-positive dogs were negative after treatment with artesunate, while 14.3% remained positive with the appearance of two new cases in the control group. Artesunate was well tolerated, and no side effects were recorded. Treatment failures were similar in both groups with 27.27% (6/22), including 18.18% (4/22) mortality in the control group, versus 26.66% (4/15), including 13.33% (2/15) mortality in the artesunate group. This is the first report showing the potential of artesunate in the treatment of dogs with clinical leishmaniasis. Artesunate showed higher efficacy than the current first-line treatment for CanL without any adverse effects. It could be a good alternative chemotherapy for CanL, and may be considered for further studies in human leishmaniases. Further clinical trials are needed to confirm these findings, to determine if there are relapses after treatment and if dogs remain infective to sandflies, to define the ideal therapeutic dosage and duration of treatment with artesunate.